Absorption pharmacokinetics and feasibility of intranasal dexmedetomidine in patients under general anaesthesia - Tiainen, Suvi-Maria; Anderson, Brian J.; Rinne, Ella; Tornio, Aleksi; Engström, Marica T.; Saari, Teijo I.; Uusalo, Panu (Wiley-Blackwell, 2025)
Background: The use of intranasal dexmedetomidine is hampered by a limited understanding of its absorption pharmacokinetics.
Methods: We examined the pharmacokinetics and feasibility of intranasal dexmedetomidine administered in the supine position to adult patients undergoing general anaesthesia. Twenty-eight patients between 35 and 80 years of age, ASA 1-3 and weight between 50 and 100 kg, who underwent elective unilateral total hip or knee arthroplasty under general anaesthesia were recruited. All patients received 100 μg of intranasal dexmedetomidine after anaesthesia induction. Six venous blood samples (at 0, 5, 15, 45, 60, 240 min timepoints from dexmedetomidine administration) were collected from each patient and dexmedetomidine plasma concentrations were measured. Concentration-time profiles after nasal administration were pooled with earlier data from a population analysis of intravenous dexmedetomidine (n = 202) in order to estimate absorption parameters using nonlinear mixed effects. Peak concentration (CMAX) and time (TMAX) were estimated using simulation (n = 1000) with parameter estimates and their associated variability.
Results: There were 28 adult patients with a mean (SD) age of 66 (8) years and weight of 83 (10) kg. The mean weight-adjusted dose of dexmedetomidine was 1.22 (0.15) μg kg-1. CMAX 0.273 μg L-1 was achieved at 98 min after intranasal administration (TMAX). The relative bioavailability of dexmedetomidine was 80% (95% CI 75-91%). The absorption half-time (TABS = 120 min; 95% CI 90-147 min) was slower than that in previous pharmacokinetic studies on adult patients. Perioperative haemodynamics of all patients remained stable.
Conclusions: Administration of intranasal dexmedetomidine in the supine position during general anaesthesia is feasible with good bioavailability. This administration method has slower absorption when compared to awake patients in upright position, with consequent concentrations attained after TMAX for several hours.